Type 2 diabetes and healthcare resource utilisation in the Kingdom of Bahrain - Rabha AbdulAziz Salman; Adel Salman AlSayyad; Craig Ludwig (BMC, 2019)
Abstract Background Type 2 diabetes is a growing health challenge in the Kingdom of Bahrain, and the disease exerts significant pressure on the healthcare system. The aim of this study was to assess the annual costs and understand the drivers of those costs in the country. Methods A sample of 628 patients diagnosed with type 2 diabetes were randomly selected from primary healthcare diabetes clinics, and the direct medical and indirect costs due to type 2 diabetes were analysed for a one-year period. The study used patients' medical records, interviews and standardised frequency questionnaires to obtain data on demographic and clinical characteristics, complication status, treatment profile, healthcare resource utilisation and absenteeism due to diabetes. The indirect costs were estimated by using the human capital approach. The direct medical and indirect costs attributable to type 2 diabetes were extrapolated to the type 2 diabetes population in Bahrain. Results In 2015, the total direct medical cost of type 2 diabetes was 104.7 million Bahraini dinars (BHD), or 277.9 million US dollars (USD), and the average unit cost per person with type 2 diabetes (1162 BHD, or 3084 USD) was more than three times higher than for a person without the condition (372 BHD, or 987 USD). The healthcare costs for patients with both micro- and macrovascular complications were more than three times higher than for patients without complications. Thus, 9% of the patients consumed 21% of the treatment costs due to complications. Complications often lead to hospital admission, and 20% of the patients consumed almost 60% of the healthcare costs attributable to type 2 diabetes due to hospital admissions. The indirect cost due to absenteeism was 1.23 million BHD (3.26 million USD). Conclusion Type 2 diabetes exerts significant pressure on Bahrain's healthcare system - primarily due to costly diabetes-related complications. It is therefore important to optimise the management and control of type 2 diabetes, thereby reducing the risk of disabling and expensive complications.